Overexpression of ZRF1 is related to tumor malignant potential and a poor outcome of gastric carcinoma. (6th December 2017) - Imamura, Taisuke; Komatsu, Shuhei; Ichikawa, Daisuke; Miyamae, Mahito; Okajima, Wataru; Ohashi, Takuma; Kiuchi, Jun; Nishibeppu, Keiji; Kosuga, Toshiyuki; Konishi, Hirotaka; Shiozaki, Atsushi; Fujiwara, Hitoshi; et al.
Abstract : ZRF1 was frequently overexpressed in GC, and the overexpression was associated with poor outcomes. Furthermore, the overexpression inhibited apoptosis, and increased proliferation, migration and invasion. These findings highlight its usefulness as a prognostic factor and therapeutic target in GC. Abstract: Zuotin-related factor 1 (ZRF1) is a recently characterized epigenetic factor involved in transcriptional regulation and is highly overexpressed in several malignancies, but it is not known whether it plays a role in gastric cancer (GC). In this study, we investigated whether ZRF1 acts as a cancer-promoting gene through its activation/overexpression in GC. We analyzed five GC cell lines and 133 primary tumors, which had been curatively resected in our hospital between 2001 and 2003. Overexpression of ZRF1 was detected in GC cell lines (four out of five lines, 80.0%) and was detected in primary tumor samples of GC (52 out of 133 cases, 39.1%) and significantly correlated with differentiated histological type, venous invasion, lymphatic invasion, advanced stage and a higher recurrence rate. ZRF1-overexpressing tumors had a worse survival rate than those with non-expressing tumors ( P < 0.01, log-rank test). ZRF1 positivity was independently associated with a worse outcome in the multivariate analysis ( P < 0.01; hazard ratio 4.92; 95% confidence interval: 1.6–21.1). In ZRF1-overexpressing GC cells, knockdown of ZRF1 using specific siRNAs inhibited the cell proliferation, migration and invasion and induced apoptosis in a p53-dependent manner. These findings suggest that ZRF1 plays a crucial role in tumor malignant potential through its overexpression and highlight its usefulness as a prognostic factor and potential therapeutic target in GC.